2020
DOI: 10.1101/2020.04.01.020479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A high-density human mitochondrial proximity interaction network

Abstract: We used BioID, a proximity-dependent biotinylation assay, to interrogate 100 mitochondrial baits from all mitochondrial sub-compartments to create a high resolution human mitochondrial proximity interaction network. We identified 1465 proteins, producing 15626 unique high confidence proximity interactions. Of these, 528 proteins were previously annotated as mitochondrial, nearly half of the mitochondrial proteome defined by Mitocarta 2.0. Bait-bait analysis showed a clear separation of mitochondrial compartmen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 100 publications
(122 reference statements)
5
59
0
Order By: Relevance
“…Similar to the other family members, SLC25A51 is predicted to contain six transmembrane regions, with its N and C termini exposed towards the mitochondrial intermembrane space ( Supplementary Fig. 1a) 33 . Functional genomics studies showed that loss of SLC25A51 can have a strong effect on cell growth 34 , although it is not strictly essential in HAP1 cells 15,16 .…”
Section: Resultsmentioning
confidence: 98%
“…Similar to the other family members, SLC25A51 is predicted to contain six transmembrane regions, with its N and C termini exposed towards the mitochondrial intermembrane space ( Supplementary Fig. 1a) 33 . Functional genomics studies showed that loss of SLC25A51 can have a strong effect on cell growth 34 , although it is not strictly essential in HAP1 cells 15,16 .…”
Section: Resultsmentioning
confidence: 98%
“…Like other members of the SLC25 family, the MCART1 protein is predicted to have six transmembrane domains, with both N and C termini facing the intermembrane space matrix based on recent proteomics proximity-labeling analysis [ Fig. 1E ; ( 9 ), topology analysis with Protter ( 10 )]. As expected, FLAG-tagged MCART1 colocalized with the inner mitochondrial membrane protein COX4 in HeLa cells (fig.…”
Section: Resultsmentioning
confidence: 99%
“…GO term analysis shows that these were enriched for mitochondrial matrix proteins involved, in particular, in mitochondrial RNA metabolism, ribosome assembly, and translation. To define whether any of these proteins were specifically enriched when GTPBP5 was used as bait, we took advantage of a larger dataset of ∼100 mitochondrial baits (published on bioRxiv ( https://doi.org/10.1101/2020.04.01.020479 ) ( 40 ) and performed specificity enrichment analysis of the preys in the GTPBP5 against the larger mitochondrial BioID dataset. The specificity enrichment analysis calculates the fold enrichment of the proximity interaction (based on the detected spectral counts) for each prey for the bait of interest (GTPBP5) and compares it to all the other baits in the dataset.…”
Section: Resultsmentioning
confidence: 99%